2021
DOI: 10.1017/s1759078721000891
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on a circular UWB antenna with Archimedean spiral slot for WLAN/Wi-MAX and satellite X-band filtering feature

Abstract: In this article a compact circular monopole antenna is represented with dimensions of 38.87 × 24.00 × 1.60 mm3 applicable for WLAN/Wi-MAX and satellite band rejection characteristics. The impedance bandwidth is 9.42 GHz (3.12–12.54 GHz) for the final antenna with an equivalent fractional bandwidth of about 120.31%, producing triple notched bands centered at 3.95, 5.20 and 8.90 GHz with assistance of Archimedean spiral slot and incorporation of defected ground structure allowing WLAN (5.2 GHz), WiMAX (3.5 GHz) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…One of the important requirements of WBANs is to have an antenna with wider bandwidth. In [21], De et al depicted that the partial ground plane antennas exhibit broader bandwidth, and in [22] Raj et al showed that antennas with defected ground plane structures like slotted ground plane have a wider bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…One of the important requirements of WBANs is to have an antenna with wider bandwidth. In [21], De et al depicted that the partial ground plane antennas exhibit broader bandwidth, and in [22] Raj et al showed that antennas with defected ground plane structures like slotted ground plane have a wider bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…It is desirable to build a patch antenna that covers two or three nearby frequency bands in certain wireless communications applications. For example, a base station antenna may be required to simultaneously provide wireless access services for both WCDMA (1.92 2.17 GHz) and WiMAX (2.50 2.69 GHz), while rejecting most of the frequencies between the two bands [1][2][3]. In this case, the center frequency ratio is 1.27.…”
Section: Introductionmentioning
confidence: 99%
“…The monopole antennas are specially used in UWB applications and circularly polarized are attracting more during the rapid development of wireless systems. Researchers are reported many simple structures with multi bands configuration which is used in wireless and satellite communication [1][2][3][4][5][6][7]). A compact multiband CPW monopole structure was presented, where a square ring with a T slot is used for achieving the wireless frequency.…”
Section: Introductionmentioning
confidence: 99%